2022
DOI: 10.3390/ijerph19053077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Face-to-Face Teaching in Addition to Electronic Learning on Personal Protective Equipment Doffing Proficiency in Student Paramedics: Randomized Controlled Trial

Abstract: Personal protective equipment doffing is a complex procedure that needs to be adequately performed to prevent health care worker contamination. During the COVID-19 pandemic, junior health care workers and students of different health care professions who had not been trained to carry out such procedures were often called upon to take care of infected patients. To limit direct contact, distance teaching interventions were used, but different trials found that their impact was rather limited. We therefore design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Psychomotor skills cannot be developed through video conferencing. For example, Currat et al found that adding face-to-face training to an e-learning module increased proficiency and enhanced skill retention in student paramedics [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychomotor skills cannot be developed through video conferencing. For example, Currat et al found that adding face-to-face training to an e-learning module increased proficiency and enhanced skill retention in student paramedics [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that the total number of tasks violated was higher in the non-face-to-face teaching with passive training group. Currat et al [38] also found that adding to a passive training (a gamified e-learning module) an active intervention (face-to-face intervention using Peyton's four-step approach) in a cohort of 65 paramedic students produced a higher proportion of doffing sequences properly performed compared to the passive intervention group (33.3%, 95% CI 18.0 to 51.8 versus 9.7%, 95% CI 2.0 to 25.8; p = 0.03). In addition, the self-assessment of the management of PPE reported by the students in our study has revealed that students felt more confident in donning and doffing after receiving face-to-face teaching with active training.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, on-line teaching methods differ significantly from each other, so it is quite important to investigate the efficiency and appropriateness of each individual method for obtaining different types of knowledge and skills. In another research, while analyzing the impact of face-to-face teaching in addition to electronic learning, Currat et al (2022) showed that live teaching improved skill acquisition and enhanced skill retention. Contrary to the stated finding, another study (Heitmann et al, 2022) examined the lecturer ratings of student's theoretical knowledge and practical skills in two clinical teaching formats, with and without patient contact, where the group without patient contact was rated significantly better by the lecturers.…”
Section: The Main Findingsmentioning
confidence: 99%
“…Ensuring conditions for acquiring knowledge in a profession that cares of the well-being of others is always a priority and, although covid measures are becoming milder and do not have an enormous impact on education currently, some innovations that arose during the pandemic may be worth keeping. The medical students experiences with online education, anxiety, perceived academic performance and obstacles related to online education Perception and the impact of online education on medical students' anxiety and perceived level of performance Rise in hours spent on online education; recorded video tutorials rated most effective; minority inform of online form as nonstimulating and difficult to engage in; less than half enjoyed online medical education; identified positive side was less time consumption Currat et al (2022) The respondents were divided into 2 groups (only online learning, and online learning + live learning)…”
Section: Introductionmentioning
confidence: 99%